Surface treatment of 25‐μm Kapton film by ammonia for improvement of TiO2/SiO2 coating's adhesion. (23rd March 2017) - Man, Yanru; Li, Zhonghua; Shu, Ming; Liu, Kai; Liu, Huitao; Gao, Yuan
Abstract : Due to a smooth hydrophobic surface of Kapton film, it is very difficult to coat an inorganic oxide coating on its surface. In this study, the surface of Kapton was treated by NH3 ·H2 O and silicon coupling agent to improve the polymer surface wettability. Changes in surface hydrophilicity were studied by contact angle measurement. The samples were irradiated by atomic oxygen (AO) in a ground‐based simulation system. TiO2 /SiO2 multi‐layer coatings were prepared on the surface of Kapton by sol–gel method to resist AO erosion. The optical transmittance and surface morphology of samples were investigated by UV–vis spectroscopy and scanning electronic microscope. The results indicated that the TiO2 /SiO2 sol could easily form a uniform thin coating on the surface of pretreated Kapton. After AO exposure, the coatings became more compact, without peeling off. The AO erosion yield value of coated Kapton was sharply down, and the samples had good optical transparency. Copyright © 2017 John Wiley & Sons, Ltd.